Safety Profile of Pertuzumab With Trastuzumab and Docetaxel in Patients From Asia With Human Epidermal Growth Factor Receptor 2‐Positive Metastatic Breast Cancer: Results From the Phase III Trial CLEOPATRA. (28th May 2014) - Swain, Sandra M.; Im, Young‐Hyuck; Im, Seock‐Ah; Chan, Valorie; Miles, David; Knott, Adam; Clark, Emma; Ross, Graham; Baselga, José
Abstract : Introduction: We report detailed safety analyses by geographic region from the phase III study CLEOPATRA with pertuzumab, trastuzumab, and docetaxel in patients with human epidermal growth factor receptor 2 (HER2)‐positive first‐line metastatic breast cancer. Patients and Methods: Patients received pertuzumab/placebo at 840 mg in cycle 1 and 420 mg in subsequent cycles, and trastuzumab at 8 mg/kg in cycle 1 and 6 mg/kg in subsequent cycles; docetaxel was initiated at 75 mg/m 2 . All study drugs were given intravenously, 3 times weekly. Results: Docetaxel dose reductions below 75 mg/m 2 were more common in patients from Asia (47.0%) than other regions (13.4%); docetaxel dose escalations to 100 mg/m 2 were less frequent in Asia (2.4%) than other regions (18.7%). Rates of edema (26.1% and 5.4% for Asia and other regions, respectively), myalgia (42.3%, 14.7%), nail disorder (39.9%, 15.1%), febrile neutropenia (18.6%, 7.1%), upper respiratory tract infection (25.7%, 10.2%), decreased appetite (47.0%, 19.1%), and rash (44.3%, 22.0%) were at least twice as high in Asia as in other regions. Adverse events did not result in a reduction in the median number of study treatment cycles administered in patients from Asia. Efficacy analyses per region showed hazard ratios similar to those of the whole intention‐to‐treat (ITT) population for progression‐free survival (ITT: 0.63; Asia: 0.68; other regions: 0.61) and overall survival (ITT: 0.66; Asia: 0.64; other regions: 0.66). Conclusion: Despite a higher proportion of docetaxel dose reductions in patients from Asia, survival benefits were comparable between regions. The benefit‐risk profile of pertuzumab, trastuzumab, and docetaxel supports this regimen as the first‐line therapy for patients with HER2‐positive metastatic breast cancer from all geographic regions. Abstract : The authors report detailed safety analyses by geographic region from the phase III study CLEOPATRA with pertuzumab, trastuzumab, and docetaxel in patients with human epidermal growth factor receptor 2 (HER2)‐positive first‐line metastatic breast cancer. Despite more docetaxel dose reductions in patients from Asia, survival benefits were comparable between regions. The benefit‐risk profile supports this regimen as the first‐line therapy for patients with HER2‐positive metastatic breast cancer from all geographic regions.